(untitled) (Dhaka University Journal of Biological Sciences, 2021)
The present study was carried out to assess the concentration of chromium (Cr), cadmium (Cd), lead (Pb), nickel (Ni), copper (Cu), zinc (Zn), iron (Fe) and manganese (Mn) in four stem vegetables such as Potato (Solanum tuberosum L.), Ginger (Zingiber officinale Roscoe), Garlic (Allium sativumL.) and Onion (Allium cepa L.) by using Atomic Absorption Spectrophotometer (AAS). Average daily intake (ADI), hazard quotient (HQ) and hazard index (HI) were also estimated to assess the human health risks posed by heavy metals from the consumption of the studied vegetables. The studied stem vegetable samples were collected in four phases from Kawran Bazar fresh vegetable market of Dhaka city of Bangladesh. Mean concentrations of Cr, Cd, Pb, Ni, Cu, Zn, Fe and Mn in the studied stem vegetables ranged between 0.88 to 2.35, 0.08 to 0.15, 0 to 2.25, 0 to 3.30, 5.70 to 9.85, 18.83 to 40.67, 50.60 to 456.38 and 9.23 to 852.35 mg/kg of dry weight, respectively. Mean concentration of maximum permissible limit (MPL) exceed in onion for Cr, in potato and onion for Pb and in ginger for Fe, Ni and Mn. Average daily intake was found to be lower than the maximum permitted tolerable daily intake in most cases except for Mn (26.475 mg/person/day) for consumption Ginger. Hazard quotient of Mn for dietary intake of Ginger (3.152) and hazard indices of Ginger (4.626), Garlic (1.183) and Onion (1.069) exceeded unity, signifying potential health risks from the dietary intake of these vegetables. This study suggests regular monitoring of heavy metals in vegetables to avoid the potential health hazards on human. Dhaka Univ. J. Biol. Sci. 30(2): 221-232, 2021 (July)